2002
DOI: 10.1088/0953-4075/35/10/317
|View full text |Cite
|
Sign up to set email alerts
|

Isotope shift studies in Zr I by Doppler-free saturated absorption spectroscopy and pseudo-relativistic Hartree-Fock calculations: II. Transitions 4d25s2-4d25s5p

Abstract: High-resolution Doppler-free saturated absorption spectroscopy has been employed to determine accurate (about ±1 MHz) isotope shifts for twenty-seven 4d25s2-4d25s5p transitions of Zr I in the green, blue and yellow-red spectral regions. These transitions, which involve an electron jump 5s→5p, represent a class in which the field shift (FS) component is larger than the specific mass shift (SMS). The SMSs and FSs were separated using a King plot procedure, in which the SMS of the 468.78 nm reference transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…It is known for some time that Hartree-Fock wave functions can provide a realistic description of the detailed behavior of the field and specific-mass contributions to the observed ISs [29]. The method of calculation used to obtain results in this work is based on the so-called pseudo-relativistic Hartree-Fock (PSUHFR) procedure [19] whose usefulness for the interpretation of IS studies was tested on Re I [30], Hf I [31], Zr I [32] and Pb I [33], etc. The relativistic FS between two isotopes or two isomers in an optical transition for light element is given by…”
Section: Isotope Shift Interpretationmentioning
confidence: 99%
“…It is known for some time that Hartree-Fock wave functions can provide a realistic description of the detailed behavior of the field and specific-mass contributions to the observed ISs [29]. The method of calculation used to obtain results in this work is based on the so-called pseudo-relativistic Hartree-Fock (PSUHFR) procedure [19] whose usefulness for the interpretation of IS studies was tested on Re I [30], Hf I [31], Zr I [32] and Pb I [33], etc. The relativistic FS between two isotopes or two isomers in an optical transition for light element is given by…”
Section: Isotope Shift Interpretationmentioning
confidence: 99%
“…In this work, for lines under consideration, ΔT NMS are located between 30 MHz and 40 MHz. The SMS needs special treatment: the King plot procedure30, which we used in many cases31–33. This may be done by plotting the corresponding shifts measured in the two spectral lines against each other for at least three different isotopes.…”
Section: Is Evaluationsmentioning
confidence: 99%
“…In our previous work on isotope shifts in Zr I [3,4] we noticed the surprising result that the experimental specific mass shifts (SMS) for some designated 4d 2 5s 2 -4d 2 5s5p transitions are larger than the SMS for the 4d 3 5s-4d 2 5s5p transitions. Since transitions involving the transfer of a d-electron are known to represent a class in which the SMS is large, we concluded that some of the experimental Zr I levels have incorrect assignments.…”
Section: Introductionmentioning
confidence: 92%
“…With the same goal in mind, we propose here the use of SMS data since for zirconium, which is a relatively light element, the SMS contributions are generally more important than the FS contributions. This procedure is more elegant since it is relatively easy to deduce SMS for considered transitions from the experimental data (table 3), by use of King plots [25], and to compare them with the predicted values (table 4) given in our previous work [4]. A large SMS indicates that the transition involves the transfer of a d-electron.…”
mentioning
confidence: 98%